Assessing policy divergence: how to investigate the differences between a law and a corresponding regulation - Carter, David P. et al (2015)
Policy designs are selected to achieve specific policy outcomes. The policy process, however, contains multiple junctures when a policy's design may diverge from its original intents. Despite this fact, few theoretically valid and methodologically reliable approaches exist to assess policy divergence as it occurs during the policy process. This article presents a method for assessing policy divergence during implementation with a comparative analysis of a legislative law and corresponding regulation. The case analysed is US organic food policy in the 1990 Organic Foods Production Act and 2002 National Organic Program regulation. The article draws theoretical leverage from Mazmanian and Sabatier's implementation framework and methodological leverage from the institutional analysis and development framework. The analysis indicates that the designs of both policies are fairly robust with relatively minor divergence. The conclusion discusses the gains and challenges in developing a comparative approach to studying policy designs and assessing policy divergence. - Reproduced.
Keywords: Public policy